Structure Dependent-Immunomodulation by Sugar Beet Arabinans via a SYK Tyrosine Kinase-Dependent Signaling Pathway - Meijerink, Marjolein; Rösch, Christiane; Taverne, Nico; Venema, Koen; Gruppen, Harry; Schols, Henk A.; Wells, Jerry M. (Frontiers in Immunology, 2018)
There is much interest in the immunomodulatory properties of dietary fibres but their activity may be influenced by contamination with microbial-associated molecular patterns (MAMPs) such as lipopolysaccharide (LPS) and lipoteichoic acids, which are difficult to remove completely from biological samples. Bone marrow-derived dendritic cells (BMDCs) from TLR2/4 knockout mice were shown to be a reliable approach to analyse the immunomodulatory properties of a diverse range of dietary fibres, by avoiding immune cell activation due to contaminating MAMPs. Several of the 44 tested dietary fibre preparations induced cytokine responses in BMDCs from TLR2/4 KO mice. The particulate fractions of linear arabinan (LA) and branched arabinan (BA) from sugar beet pectin were shown to be strongly immune stimulatory with LA being more immune stimulatory than BA. Enzymatic debranching of BA increased its immune stimulatory activity, possibly due to increased particle formation by the alignment of debranched linear arabinan. Mechanistic studies showed that immune stimulation was independent of the Dectin-1 receptor but Syk kinase-dependent suggesting recognition of the LA and BA via an unknown C-type lectin receptor.